Design projecting of clothing collections based on the transformation of the forms of women’s costume of the 1920s - Krasniuk, Larysa; Troyan , Oleksandr; Lushchevska, Olena; Pryvala, Valeriy; Novak, Olha (Art and Design, 2026)
The relevance of the study is determined by the need to explore new creative techniques for developing original clothing collections distinguished by artistic expressiveness, high aesthetic quality, and strong emotional content. The aim of the research was to develop artistic design projects for women’s clothing collections inspired by the women’s costume of the 1920s. The research methods included the study of creative sources, which involved analysing silhouettes, shapes, characteristic lines, proportions, colour schemes, textures, decoration, accessories, and complementary elements. The morphological analysis method applied in the study entailed generating new ideas through the reinterpretation and transformation of the source of inspiration into forms of contemporary clothing. The research also involved the selection and stylisation of compositional elements of form creation, the implementation of the project in material, and the testing of design solutions within the context of fashion design competitions. As a result, an artistic and compositional analysis of the source of inspiration was carried out, identifying the key shapes, silhouettes, proportions, decorations, and colours of the chosen reference. The core idea of the project was formulated, reflecting the authors’ individual vision of the inspirational source. A mood board was created, encapsulating the authors’ conceptual vision for the designed collections. Four variations of creative